2011
DOI: 10.1111/j.1472-4642.2011.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

When the method for mapping species matters: defining priority areas for conservation of African freshwater turtles

Abstract: Aim  Defining priority areas for conservation is essential to minimize biodiversity loss, but the adoption of different methods for describing species distributions influences the outcomes. In order to provide a robust basis for the conservation of freshwater turtles in Africa, we compared the effect that different species‐mapping approaches had on derived patterns of species richness, species vulnerability and protected‐area representativeness.Location  Africa.Methods  We adopted three different approaches wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…To analyse the spatial distribution of Italian coastal EU habitats contained in VegDunes, the information associated with each relevé was transferred into a 10 km x 10 km UTM grid, which is the spatial resolution most commonly used in regional and national analyses (Hassall & Thompson 2010), using a GIS software (ESRI Inc. 2006). Grid squares are commonly used to analyse habitats and species distribution patterns because this simple method is applicable to any amount of data (Bombi et al 2011). In fact, information on the habitat types and species listed in the Annexes of the Habitats Directive (EEC 1992) has been aggregated at European level and organised on the UTM grid (European Commission 2008).…”
Section: Brief Analysis Of the Information In Vegdunes And Spatial DImentioning
confidence: 99%
“…To analyse the spatial distribution of Italian coastal EU habitats contained in VegDunes, the information associated with each relevé was transferred into a 10 km x 10 km UTM grid, which is the spatial resolution most commonly used in regional and national analyses (Hassall & Thompson 2010), using a GIS software (ESRI Inc. 2006). Grid squares are commonly used to analyse habitats and species distribution patterns because this simple method is applicable to any amount of data (Bombi et al 2011). In fact, information on the habitat types and species listed in the Annexes of the Habitats Directive (EEC 1992) has been aggregated at European level and organised on the UTM grid (European Commission 2008).…”
Section: Brief Analysis Of the Information In Vegdunes And Spatial DImentioning
confidence: 99%
“…Typically resource selection functions are used to map suitable habitat based on predicted probability of use but the spatial resolution selected to obtain data to enter the models influences the accuracy of predictions (Meyer and Thuiller 2006;Baker et al 2007) and does not affect models equally across regions, techniques, or species types (Carter et al 2006;Guisan et al 2007). Consequently, failure to consider and select the most appropriate scale or suite of scales (domain) may lead to incorrect interpretations of data and consequently the mismanagement of critical natural resources (Bowyer and Kie 2006;Bombi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated the countries in the Gulf of Guinea coast, the Guinea-Congo rain forest region, and the Albertine Rift to be the most important areas of the African continent in terms of freshwater turtle species richness [18,10], whereas South Africa is the most relevant area for the terrestrial species [18]. Our study revealed that, in terms of relative uniqueness (due to lower rates of spatial turnover at country level), some of the Gulf of Guinea countries (i.e.…”
Section: Ranking African Countriesmentioning
confidence: 99%
“…In Sub-Saharan Africa, turtles and tortoises are exposed to several threats, including intense hunting for food and traditional medicine, habitat loss, collection for the pet trade, etc. [8][9]; however, global studies analyzing their ecological and biogeographic patterns at the African continent scale and the implications for conservation, have been rarely performed [9][10].…”
Section: Introductionmentioning
confidence: 99%